Minimally invasive direct coronary artery bypass and TAVI: Timing and considerations in octogenarians: A case report. (November 2017) - Langenaeken, Tom; De Raeymaeker, Xavier; De Poortere, Aaron; Rega, Filip; Oosterlinck, Wouter
Abstract : Introduction: Coronary artery disease is frequently associated with aortic stenosis. Using minimally invasive direct coronary artery bypass (MIDCAB), we conducted a single bypass of the LAD using the LIMA on an 87-year-old patient with TAVI-prothesis and pacemaker. This case report describes the procedure for our rather special patient, from intake to discharge. Case description: A 87-year-old male was admitted to our hospital due to NONSTEMI. Surgical history included TAVI Corevalve® endoprothesis (81y.o.) and BIOTRONIK pacemaker for left bundle branch block. We opted for minimally invasive direct coronary artery bypass (MIDCAB) using the Da Vinci® Robot System. There were no adverse events in the postoperative period. Patient was discharged on the 8 th postoperative day. Several questions arose while treating our rather complex patient: what is the optimal timing for revascularization after TAVI and what method of revascularization should be used? Results and Conclusions: We consider TAVI followed by MIDCAB as a feasible approach for these complex patients. It is potentially beneficial regarding blood loss and hospital stay. The staged approach avoids many risks described in literature. Research is needed to support this intuitive assumption; the effect of TAVI on coronary hemodynamics on the long term as well as comparing combined and staged TAVI-MIDCAB could be interesting subjects for further investigation. Take home message: A staged minimal invasive procedure with TAVI and followed by MIDCAB might be beneficial in octogenarians.